Secondary battery, battery module, battery pack and power consuming device

By optimizing separator porosity, electrolyte viscosity, and film-forming additives, the secondary battery design addresses rapid charging and cycle life challenges, achieving enhanced performance and stability through optimized lithium ion transfer and protective film formation.

JP2025502232AActive Publication Date: 2025-01-24CONTEMPORARY AMPEREX TECHNOLOGY (HONG KONG) LIMITED
View PDF 5 Cites 0 Cited by

Patent Information

Application Number
JP2024541894
Authority / Receiving Office
JP · JP
Patent Type
Applications
Current Assignee / Owner
Filing Date
2022-07-15
Publication Date
2025-01-24
Estimated Expiration
2042-07-15

AI Technical Summary

Technical Problem

Existing secondary batteries face challenges in achieving high discharge performance and cycle life, particularly in rapid charging and maintaining structural stability of active materials due to side reactions between the active material surface and electrolyte.

Method used

The secondary battery design includes a specific porosity of the separator, viscosity of the electrolyte, and content of film-forming additives to optimize lithium ion transfer rates, forming protective films on the active material surfaces to reduce side reactions and enhance structural stability.

Benefits of technology

This design improves the rapid charging ability and cycle life of secondary batteries by enhancing lithium ion transfer rates and reducing side reactions, resulting in improved performance and longevity.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 2025502232000001_ABST
    Figure 2025502232000001_ABST
Patent Text Reader

Abstract

The present invention provides a secondary battery, a battery module, a battery pack, and a power consumption device. The secondary battery includes a positive electrode sheet, a negative electrode sheet, a separator, and an electrolyte, the positive electrode sheet includes a positive electrode active material, the negative electrode sheet includes a negative electrode active material, the separator is provided between the positive electrode sheet and the negative electrode sheet, the electrolyte includes a first organic solvent and a film-forming additive, the film-forming additive is arranged to form an interfacial film on the surface of the positive electrode active material and / or the negative electrode active material, and the porosity of the separator is ε%, the mass percentage content of the film-forming additive relative to the total mass of the electrolyte is b%, and the viscosity value of the electrolyte at 25°C is c (mPa·s), the secondary battery satisfies 4≦(b*ε) / c≦240. The present invention can improve the rapid charge / discharge performance and cycle life of the secondary battery. Figure 1
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present application relates to the field of batteries, and in particular to secondary batteries, battery modules, battery packs and power consuming devices. [Background technology]

[0002] 2. Description of the Related Art Secondary batteries have characteristics such as high capacity and long life, and are therefore widely used in electronic devices such as mobile phones, laptops, electric scooters, electric cars, electric airplanes, electric boats, electric toy cars, electric toy boats, electric toy airplanes, and power tools.

[0003] As the range of applications of batteries becomes wider, the requirements for the performance of secondary batteries become more stringent. For example, the secondary batteries are required to have excellent rapid charge / discharge performance and cycle life. Therefore, improvement of the rapid charge / discharge performance and cycle life of secondary batteries is also an issue that needs to be resolved as soon as possible. Summary of the Invention

[0004] The present application has been made in view of the above-mentioned problems, and has an object to provide a secondary battery, a battery module, a battery pack, and a power consuming device.

[0005] A first aspect of the present application provides a secondary battery, the secondary battery comprising: a positive electrode sheet, a negative electrode sheet, a separator, and an electrolyte, the positive electrode sheet comprising a positive electrode active material, the negative electrode sheet comprising a negative electrode active material, the separator being provided between the positive electrode sheet and the negative electrode sheet, the electrolyte comprising a first organic solvent and a film-forming additive, the film-forming additive being disposed so as to form an interfacial film on a surface of the positive electrode active material and / or the negative electrode active material, wherein, when the porosity of the separator is ε%, the mass percentage content of the film-forming additive relative to the total mass of the electrolyte is b%, and the viscosity value of the electrolyte at 25°C is c (mPa s), the secondary battery satisfies 4≦(b*ε) / c≦240, and selectably satisfies 4≦(b*ε) / c≦180.

[0006] Thus, in the present application, the porosity of the separator, the viscosity value of the electrolyte, and the film-forming additive are adjusted to satisfy the above ranges, and the lithium ion migration speed in the solid phase mass transfer and the liquid phase mass transfer are adjusted comprehensively, thereby improving the average migration speed of the lithium ion and improving the rapid charging ability of the secondary battery. In addition, the film-forming additive can not only adjust the viscosity of the electrolyte to further adjust the lithium ion migration speed in the liquid phase, but also form a protective layer on the surface of the active material to passivate the surface of the active material, reduce the risk of side reactions occurring between the surface of the active material and the electrolyte, improve the structural stability of the active material, and improve the cycle life of the secondary battery. Here, the film-forming additive, especially the lithium salt-based additive, is advantageous in that the solid electrolyte interfacial film formed on the surface of the negative electrode active material has a relatively small impedance, and is more advantageous for the insertion and desorption of lithium ions.

[0007] In any embodiment, the secondary battery further satisfies at least one of conditions (1) to (3): (1) 25≦ε≦55, and optionally 30≦ε≦50; (2) 0.1≦b≦8, and optionally 0.1≦b≦6; (3) 1≦c≦6, and optionally 2≦c≦5.

[0008] Thus, when the porosity of the separator of the present application is within the above range, the porosity of the separator is not too small, its liquid permeability is good, and its lithium ion permeability is strong, which is favorable for lithium ions to move to the adjacent active material through the separator, and the rapid charging ability of the secondary battery can be further improved. When the mass percentage content of the film-forming additive is within the above range, the film-forming additive can undergo a film-forming reaction with the active material to form a dense and uniform film layer. This provides good protection for the active material, and the film-forming additive, such as a lithium salt-based additive, can form an SEI film with a small film-forming impedance, so that both life and power can be achieved. When the viscosity value of the electrolyte is within the above range, the viscosity of the electrolyte is not too large, and its ion conductivity is relatively high, which is favorable for improving the ion transmission rate, and the rapid charging ability of the secondary battery can be improved. In addition, when the viscosity of the electrolyte is within the above range, the compatibility between the electrolyte and the positive and negative electrode sheets is relatively good, and side reactions with the active materials in the positive and negative electrode sheets are unlikely to occur, thereby improving the cycle stability of the secondary battery.

[0009] In any embodiment, when the mass percentage content of the first organic solvent relative to the total mass of the electrolyte solution is a%, the secondary battery further satisfies 2≦c+2*a%≦8.

[0010] Therefore, in the present application, by adjusting the mass percentage content of the first organic solvent, it is possible to adjust the viscosity of the electrolyte solution within an appropriate range, and a stable interfacial film can be formed during the film formation process to completely cover the active material surface.

[0011] In any embodiment, 60≦a≦90, and optionally 65≦a≦85.

[0012] In any embodiment, the first organic solvent comprises one or more of a linear carbonate solvent, a carboxylic acid ester solvent, and a nitrile solvent; optionally, the linear carbonate solvent comprises one or more of ethyl methyl carbonate (EMC), diethyl carbonate (DEC), dimethyl carbonate (DMC), and methyl propyl carbonate (MPC); optionally, the carboxylic acid ester solvent comprises one or more of ethyl acetate (EA), methyl acetate (MA), ethyl propionate (EP), methyl formate (MF), ethyl butyrate (EB), butyl acetate (BA), methyl propionate (MP), methyl butyrate (MB), propyl butyrate (PB), and butyl butyrate (BB); optionally, the nitrile solvent comprises one or more of acetonitrile (AN), glutaronitrile (GLN), and adiponitrile (ADN).

[0013] As a result, the viscosity range of the entire electrolyte can be adjusted within an appropriate range because the viscosity of the above-mentioned solvent of the present application is low. In addition, when the first organic solvent contains two or more types, the viscosity and ionic conductivity of the electrolyte can be adjusted synergistically, and multiple types of solvents can participate in the membrane formation reaction, so that the membrane layer structure contains multiple types of components, and the stability of the interface membrane can be improved.

[0014] In an optional embodiment, the film-forming additive includes an anode film-forming additive arranged to form an interfacial film on a surface of an anode active material, the mass percentage content of the anode film-forming additive relative to the total mass of the electrolyte being b1%, and a cathode film-forming additive arranged to form an interfacial film on a surface of a cathode active material, the mass percentage content of the cathode film-forming additive relative to the total mass of the electrolyte being b2%, and the secondary battery satisfies 1≦b2 / b1≦60 and optionally satisfies 1≦b2 / b1≦40.

[0015] Therefore, in the present application, when the contents of the negative electrode film-forming additive and the positive electrode film-forming additive are adjusted to satisfy the above formula, the electrolyte can form an SEI film on the surface of the negative electrode active material, and a CEI film on the surface of the positive electrode active material. In addition, the interface impedance of the two membrane layers is relatively low, the kinetic activity is good, and the charge transfer impedance in the secondary battery is small, which is favorable for the rapid migration of lithium ions and can improve the rapid charging performance of the secondary battery.

[0016] In any embodiment, 0.01≦b1≦1.5 and / or 0.1≦b2≦7. When the film-forming additive is in the above range, it can form a dense and stable interfacial film on the surface of the active material, which can fully protect the active material, improve the structural stability of the active material, and ensure the cycle stability of the secondary battery.

[0017] In any embodiment, the additive for forming the negative electrode film includes one or more of a boron-containing lithium salt, a phosphorus-containing lithium salt, and a sulfur-containing lithium salt, and optionally the boron-containing lithium salt includes one or more of lithium tetrafluoroborate LiBF4, lithium disoxalate borate LiBOB, and lithium difluorooxalate borate LiDFOB, and optionally the phosphorus-containing lithium salt includes one or more of lithium difluorophosphate LiPO2F2, lithium fluorophosphate Li2PO3F, and lithium phosphate Li3PO4, and optionally the sulfur-containing lithium salt includes one or more of lithium fluorosulfonate LiFSO3, lithium sulfate Li2SO4, and lithium sulfamate LiSO3NH2.

[0018] As a result, the boron-containing lithium salt of the present invention can form an SEI film with a stable structure and a relatively small impedance value on the surface of the negative electrode active material, thereby improving the high and low temperature performance of the secondary battery. x PO y F zand LiF component-rich SEI film can be formed. The SEI film has low interface impedance and can significantly improve the cycle performance of the secondary battery. The sulfur-containing lithium salt can form a dense and stable SEI film on the surface of the negative electrode active material, and can further improve the protection performance for the negative electrode active material.

[0019] In any embodiment, the positive electrode film-forming additive includes a carbonate-based additive and / or a sulfate-based additive, and optionally the carbonate-based additive includes one or more of vinylene carbonate VC, fluoroethylene carbonate FEC, difluoroethylene carbonate DFEC, vinyl ethylene carbonate VEC, and dioctyl carbonate CC, and optionally the sulfate-based additive includes a cyclic sulfonate-based additive and / or a hydrocarbon group sulfate-based additive, and further optionally the cyclic sulfonate-based additive includes one or more of 1,3-propane sultone PS, propylene sultone PES, and 3-fluoro-1,3-propane sultone FPS, and the hydrocarbon group sulfate-based additive includes one or more of vinyl sulfate DTD, diethyl sulfate DES, and dimethyl sulfate DMS.

[0020] Thus, the carbonate-based additive of the present application has a strong dielectric constant and dissolves lithium salt to a greater extent, which allows the lithium salt to dissociate lithium ions more easily and improves the conductivity of the electrolyte, and can be mixed with the first organic solvent to better adjust the dielectric constant and viscosity of the electrolyte, thereby improving the ionic conductivity of the secondary battery and further improving the electrochemical window of the secondary battery. The sulfate-based additive can form a dense and stable film layer and can provide good protection for the active material.

[0021] In any embodiment, the electrolyte further comprises a lithium salt, the lithium salt comprises one or more of lithium hexafluorophosphate LiPF6, lithium bisfluorosulfonyl imide LiFSI and lithium bistrifluoromethylsulfonyl imide LiTFSI, and optionally the mass percentage content of the lithium salt relative to the total mass of the electrolyte is d%, 5%≦d≦25%, and further optionally 10%≦d≦20%. The lithium salt is regarded as a complex of lithium ion and anion group, and has an important effect on the electrolyte. The lithium salt has thermal stability and high electrical conductivity.

[0022] In an optional embodiment, the separator includes a substrate layer and a coating layer provided on a surface of the substrate layer, the substrate of the substrate layer includes one or more of polyethylene, polypropylene, polyparaphenylene terephthalamide, polyethylene terephthalate, polytetrafluoroethylene, polyacrylonitrile, polyimide, and polyamide, and / or the coating layer includes a ceramic coating layer and / or a polymer coating layer, optionally, the ceramic particles in the ceramic coating layer include one or more of SiO2, Al2O3, AlOOH, CaO, TiO2, MgO, ZnO, ZrO2, Mg(OH)2, and BaSO4, and the polymer material of the polymer coating layer includes one or more of polyethylene PE, polypropylene PP, polyparaphenylene terephthalamide PPTA, polyethylene terephthalate PET, polytetrafluoroethylene PTFE, polyacrylonitrile PAN, polyimide PI, and polyamide PA.

[0023] As a result, the substrate layer of the present invention has good permeability to lithium ions, which is advantageous for the movement of lithium ions, and a coating layer is provided on the surface of the substrate layer, which can further improve the mechanical properties of the separator.

[0024] A second aspect of the present application further provides a battery module including a secondary battery according to any one of the embodiments of the first aspect of the present application.

[0025] A third aspect of the present application further provides a battery pack including a battery module according to an embodiment of the second aspect of the present application.

[0026] A fourth aspect of the present application further provides a power consuming device comprising a secondary battery according to any one of the embodiments of the first aspect of the present application, a battery module according to an embodiment of the second aspect of the present application, or a battery pack according to an embodiment of the third aspect of the present application. [Brief description of the drawings]

[0027] In order to more clearly describe the technical solutions of the embodiments of the present application, the following briefly describes the drawings that need to be used in the embodiments of the present application. Obviously, the drawings described below are only some embodiments of the present application, and those skilled in the art can also obtain other drawings based on the drawings without creative labor.

[0028] [Figure 1] FIG. 1 is a schematic diagram of one embodiment of a secondary battery of the present application.

[0029] [Diagram 2] FIG. 2 is an exploded schematic view of the embodiment of the secondary battery of FIG. 1.

[0030] [Diagram 3] FIG. 1 is a schematic diagram of one embodiment of a battery module of the present application.

[0031] [Figure 4] FIG. 1 is a schematic diagram of one embodiment of a battery pack of the present application.

[0032] [Diagram 5] 5 is an exploded schematic view of the embodiment of the battery pack shown in FIG. 4.

[0033] [Figure 6]1 is a schematic diagram of one embodiment of a power consuming device including a secondary battery of the present application as a power source.

[0034] The drawings are not necessarily drawn to scale.

[0035] The explanation of the symbols is as follows.

[0036] 1 Battery pack 2 Upper case 3 Lower housing 4 Battery Module

[0037] 5 Secondary battery 51 Housing 52 Electrode Assembly

[0038] 53 Cover plate

[0039] 6 Power consumption equipment DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0040] Hereinafter, embodiments specifically disclosing the secondary battery, battery module, battery pack, and power consumption device of the present application will be described in detail. However, unnecessary detailed description may be omitted. For example, detailed description of already well-known matters and duplicate description of substantially the same configuration may be omitted. This is to avoid the following description becoming unnecessarily redundant and to facilitate understanding by those skilled in the art. Note that the accompanying drawings and the following description are provided to enable those skilled in the art to fully understand the present application, and are not intended to limit the subject matter described in the claims.

[0041] The "ranges" disclosed herein are defined in the form of lower and upper limits, where a given range is defined by selecting one lower limit and one upper limit, and the selected lower and upper limits specifically define the boundaries of the range. Ranges defined in this manner may be inclusive or exclusive of the end values ​​and may be arbitrarily combined, i.e., any lower limit may be combined with any upper limit to form a range. For example, by listing ranges of 60-120 and 80-110 for a particular parameter, it is understood that ranges of 60-110 and 80-120 are also contemplated. Also, by listing minimum range values ​​1 and 2 and maximum range values ​​3, 4 and 5, the ranges 1-3, 1-4, 1-5, 2-3, 2-4 and 2-5 are all contemplated. In this application, unless otherwise stated, a numerical range "a-b" refers to a contraction of any real number combination between a and b, where a and b are both real numbers. For example, the numerical range "0 to 5" indicates that all real numbers between "0 and 5" are listed herein, and "0 to 5" is a contraction of combinations of these numerical values. In addition, when a parameter is expressed as an integer ≧2, this is equivalent to disclosing that the parameter is an integer such as 2, 3, 4, 5, 6, 7, 8, 9, 10, 11, 12, etc.

[0042] Unless otherwise stated, all embodiments and optional embodiments of the present application can be combined with each other to form a new technical solution.Unless otherwise stated, all technical features and optional technical features of the present application can be combined with each other to form a new technical solution.

[0043] Unless otherwise stated, all steps in the present application may be performed in sequence, may be performed randomly, and are preferably performed in sequence. For example, a method includes steps (a) and (b) indicates that the method may include steps (a) and (b) performed in sequence, and may include steps (b) and (a) performed in sequence. For example, a method may further include step (c) indicates that step (c) may be added to the method in any order, e.g., the method may include steps (a), (b), and (c), may include steps (a), (c), and (b), and may further include steps (c), (a), and (b), etc.

[0044] Unless otherwise stated, the terms "comprising" and "including" referred to in this application may be open ended or closed ended. For example, "comprising" and "including" indicate that the term may comprise or include other components not further recited, or may comprise or include only the recited components.

[0045] In this application, unless otherwise stated, the term "or" is inclusive. For example, the phrase "A or B" means "A, B, or both A and B." More specifically, any of the following conditions satisfy the condition "A or B": A is true (or exists) and B is false (or does not exist), A is false (or does not exist) and B is true (or exists), or A and B are both true (or exist).

[0046] As used herein, the terms "plurality" and "species" refer to two or more than two species.

[0047] In the present application, the secondary battery may include a lithium ion battery, a lithium sulfur battery, a sodium lithium ion battery, a sodium ion battery, or a magnesium ion battery, but the embodiments of the present application are not limited thereto.

[0048] The secondary battery includes an electrode assembly consisting of a positive electrode sheet, a negative electrode sheet, and a separator, and an electrolyte. The secondary battery mainly operates by metal ions moving between the positive electrode sheet and the negative electrode sheet, the positive electrode sheet including a positive electrode active material, and the negative electrode sheet including a negative electrode active material. In this specification, the metal ions may be lithium ions, sodium ions, etc., and the charging process will be described below with the metal ions being lithium ions.

[0049] In the charging process of a secondary battery, the electrode kinetics process usually includes: (1) a lithium ion desorption step, in which lithium ions are desorbed from the positive electrode active material and transferred to the electrolyte phase; (2) a liquid phase mass transfer step in the electrolyte phase, in which the solvated lithium ions in the electrolyte diffuse and transfer to the surface of the negative electrode active material; (3) a surface conversion step, in which the solvated lithium ions adsorb and react on the surface of the negative electrode active material during the first charge to form a solid electrolyte interface (SEI) film, and in the subsequent charging process, the solvated lithium ions adsorb on the surface of the SEI film, and after a desolvation process, the lithium ions reach the surface of the negative electrode active material; (4) a charge exchange step, in which the lithium ions obtain electrons from the surface of the negative electrode active material to form a lithium insertion product; and (5) a solid phase mass transfer step of the lithium insertion product, in which the lithium insertion product diffuses from the surface of the negative electrode active material to the inside, completing the charging process.

[0050] With the improvement of the charging rate, it is required that lithium ions are rapidly desorbed from the positive electrode active material and inserted into the negative electrode active material during the charging and discharging process, and lithium ions are rapidly desorbed from the negative electrode active material and inserted into the positive electrode active material during this process, and the solid phase mass transfer and liquid phase mass transfer of lithium ions are both limiting factors that affect the lithium ion transfer rate, which has a significant impact on the rapid charging performance of secondary batteries. In addition, side reactions may occur between the active material surface and the electrolyte during the charging and discharging process, which may destroy the structure of the active material, significantly shorten its life, and reduce the cycle life of the secondary battery.

[0051] Therefore, the inventors propose a secondary battery that improves the rapid charging performance of the secondary battery by improving the lithium ion transfer rate in solid phase mass transfer and liquid phase mass transfer, and also improves the structural stability of the active material by protecting the surface of the active material, thereby improving the cycle stability of the secondary battery and improving the cycle life of the secondary battery. Next, the technical solution of the present application will be described in detail.

[0052] secondary battery

[0053] According to a first aspect, the present application provides a secondary battery. A secondary battery, also called a rechargeable battery or storage battery, refers to a battery that can be continuously used by activating an active material by charging after the battery is discharged.

[0054] The secondary battery includes a positive electrode sheet, a negative electrode sheet, a separator, and an electrolyte, the positive electrode sheet includes a positive electrode active material, the negative electrode sheet includes a negative electrode active material, the separator is provided between the positive electrode sheet and the negative electrode sheet, the electrolyte includes a first organic solvent and a film-forming additive, the film-forming additive is arranged to form an interfacial film on a surface of the positive electrode active material and / or the negative electrode active material, and the porosity of the separator is ε%, the mass percentage content of the film-forming additive relative to the total mass of the electrolyte is b%, and the viscosity value of the electrolyte at 25°C is c (mPa s), the secondary battery satisfies 4≦(b*ε) / c≦240.

[0055] Although the mechanism is not clear, the reason why the present application can simultaneously improve the rapid charging performance and cycle life of a secondary battery is speculated to be as follows.

[0056] In the process of lithium ions moving from the positive electrode sheet to the negative electrode sheet, they must first move from the positive electrode sheet to the separator, and then move from the separator to the negative electrode sheet. Therefore, the porosity of the separator has a certain effect on the lithium ion movement speed, and therefore, in this application, the porosity of the separator is one of the variables to be controlled in this application.

[0057] In the liquid phase mass transfer process, lithium ions move in the electrolyte, and the viscosity of the electrolyte has a certain effect on the migration speed of lithium ions, and the smaller the viscosity, the more favorable it is for the migration of lithium ions, so the viscosity of the electrolyte has a certain effect on the migration speed of lithium ions, which is another variable controlled in the present application. Since the first organic solvent, as the main component of the electrolyte, has a significant effect on the viscosity of the electrolyte, the viscosity of the electrolyte can be adjusted by selecting the first organic solvent. Of course, the film-forming additive also has a certain effect on the viscosity of the electrolyte, so the electrolyte can determine the final viscosity of the electrolyte by selecting the first organic solvent and controlling the mass percentage content of the film-forming additive. When the viscosity of the electrolyte is within a suitable range, it can well infiltrate the separator. During the charge and discharge process of the secondary battery, it contributes to the rapid reflux of the electrolyte and the rapid transport of lithium ions.

[0058] In the present application, the porosity of the separator, the viscosity value of the electrolyte, and the film-forming additive are adjusted to satisfy the above ranges, and the lithium ion migration speed in the solid phase mass transfer and the liquid phase mass transfer are adjusted comprehensively, thereby improving the average migration speed of the lithium ion and improving the rapid charging ability of the secondary battery. In addition, the film-forming additive can not only adjust the viscosity of the electrolyte to further adjust the lithium ion migration speed in the liquid phase, but also form a protective layer on the surface of the active material to passivate the surface of the active material, reduce the risk of side reactions occurring between the surface of the active material and the electrolyte, improve the structural stability of the active material, and improve the cycle life of the secondary battery. Here, the film-forming additive, especially the lithium salt-based additive, is advantageous in that the solid electrolyte interface (SEI) film formed on the surface of the negative electrode active material has a relatively small impedance and is more advantageous for the insertion and desorption of lithium ions. Of course, the film-forming additive may be other types of additives such as ester-based additives.

[0059] Alternatively, 4≦(b*ε) / c≦180, and illustratively, (b*ε) / c may be 4, 5, 8, 10, 12, 15, 18, 20, 25, 30, 40, 50, 60, 70, 80, 90, 100, 120, 150, 160, 170, 180, 190, 200, 210, 220, or 240, or may be a range consisting of any two of the above values.

[0060] In some embodiments, 25≦ε≦55.

[0061] When the porosity of the separator is within the above range, the porosity of the separator is not too small, its liquid permeability is good, and the lithium ion permeability is strong, which is favorable for lithium ions to move to the adjacent active material through the separator, and the rapid charging ability of the secondary battery can be further improved. The porosity of the separator is not too large, which reduces the risk of the positive electrode sheet and the negative electrode sheet directly contacting each other to cause a short circuit, and the separator has good mechanical performance, so that even if dendrites are formed inside the secondary battery, the separator is not likely to be broken and cause a short circuit, and the safety performance of the secondary battery can be ensured. Preferably, 30≦ε≦50, and for example, the porosity ε% of the separator may be 25%, 28%, 30%, 32%, 35%, 38%, 40%, 42%, 45%, 46%, 48%, 50%, 52%, 53%, 54% or 55%, or may be a range consisting of any two of the above values.

[0062] In some embodiments, 0.1≦b≦8.

[0063] When the mass percentage content of the film-forming additive is within the above range, the film-forming additive can undergo a film-forming reaction with the active material to form a dense and uniform film layer. This provides good protection for the active material, and the film-forming additive, such as a lithium salt-based additive, can form an SEI film with a small film-forming impedance, thereby achieving both life and power. Preferably, 0.1≦b≦6, and for example, the mass percentage content b% of the film-forming additive can be 0.1%, 0.5%, 0.8%, 1%, 1.5%, 1.8%, 2%, 2.5%, 3%, 3.5%, 4%, 4.5%, 5%, 5.5%, 6%, 6.5%, 7%, 7.5% or 8%, or can be a range consisting of any two of the above values.

[0064] In some embodiments, 1≦c≦6.

[0065] When the viscosity value of the electrolyte is within the above range, the viscosity of the electrolyte is not too high, and the ion conductivity is relatively high, which is favorable for improving the ion transmission rate, and can improve the rapid charging ability of the secondary battery. In addition, when the viscosity of the electrolyte is within the above range, the compatibility of the electrolyte with the positive and negative electrode sheets is relatively good, and side reactions with the active materials in the positive and negative electrode sheets are unlikely to occur, so that the cycle stability of the secondary battery can be improved. Preferably, 2≦c≦5, and for example, the viscosity c (mPa·s) of the electrolyte may be 1 mPa·s, 1.5 mPa·s, 2 mPa·s, 2.5 mPa·s, 3 mPa·s, 3.5 mPa·s, 4 mPa·s, 4.5 mPa·s, 5 mPa·s, 5.5 mPa·s, or 6 mPa·s, or may be a range consisting of any two of the above values.

[0066] In some embodiments, the mass percentage content of the first organic solvent relative to the total mass of the electrolyte is represented by a, and the secondary battery further satisfies 2≦c+2*a%≦8.

[0067] By adjusting the mass percentage content of the first organic solvent, the viscosity of the electrolyte can be adjusted within a suitable range, and a stable interfacial film can be formed during the film formation process, and the active material surface can be completely covered. Illustratively, c+2*a% can be 2, 2.5, 3, 3.5, 4, 4.5, 5, 5.5, 6, 6.5, 7, 7.5 or 8, or can be within a range consisting of any two of the above values.

[0068] In some embodiments, 60≦a≦90, preferably 65≦a≦85. Exemplarily, the mass percentage content a% of the first organic solvent relative to the total mass of the electrolyte may be 60%, 65%, 70%, 75%, 80%, 85% or 90%, or may be a range consisting of any two of the above values.

[0069] In some embodiments, the first organic solvent comprises one or more of linear carbonate solvents, carboxylic acid ester solvents, and nitrile solvents. The viscosity of the solvent is low, so the viscosity range of the entire electrolyte can be adjusted within an appropriate range. In addition, when the first organic solvent comprises two or more types, the viscosity and ionic conductivity of the electrolyte can be adjusted synergistically, and multiple types of solvents can participate in the membrane formation reaction, so that the membrane layer structure comprises multiple types of components, and the stability of the interface membrane can be improved.

[0070] Examples of linear carbonate-based solvents include one or more of ethyl methyl carbonate (EMC), diethyl carbonate (DEC), dimethyl carbonate (DMC) and methyl propyl carbonate (MPC). The linear carbonate-based solvent has a relatively low viscosity, is favorable for ionic conductivity, and has high electrochemical stability and a high electrochemical window.

[0071] Examples of the carboxylate-based solvent include one or more of ethyl acetate EA, methyl acetate MA, ethyl propionate EP, methyl formate MF, ethyl butyrate EB, butyl acetate BA, methyl propionate MP, methyl butyrate MB, propyl butyrate PB, and butyl butyrate BB. The carboxylate-based solvent has a relatively low viscosity, and the combination of multiple carboxylate-based solvents can provide the electrolyte with a lower surface tension.

[0072] As an example of nitrile-based solvent, said nitrile-based solvent includes one or more of acetonitrile AN, glutaronitrile GLN and adiponitrile ADN. The above-mentioned nitrile-based solvent has a relatively low viscosity and a relatively high dielectric constant, which is advantageous for improving the migration speed of lithium ions, and the stability of said nitrile-based solvent is high, which makes it difficult to cause side reactions with the surface of active material, thereby ensuring the structural stability of active material and the cycle stability of secondary battery.

[0073] In some embodiments, the electrolyte may further include a second organic solvent, and the second organic solvent may include an ether-based solvent, etc. The ether-based solvent also has a relatively low viscosity, which is advantageous for further improving the viscosity of the entire electrolyte. In addition, the ether-based solvent is advantageous for allowing the lithium in the secondary battery to maintain a good morphology during the charge-discharge cycle, improving the cycle stability of the secondary battery, and improving the cycle life of the secondary battery.

[0074] As an example of the ether-based solvent, the ether-based solvent may include ether, etc.

[0075] In some embodiments, the film-forming additive includes an anode film-forming additive and a cathode film-forming additive, the anode film-forming additive is arranged to form an interfacial film on a surface of the anode active material, and a mass percentage content of the anode film-forming additive relative to the total mass of the electrolyte is b1%, the cathode film-forming additive is arranged to form an interfacial film on a surface of the cathode active material, and a mass percentage content of the cathode film-forming additive relative to the total mass of the electrolyte is b2%, and the secondary battery satisfies 1≦b2 / b1≦60.

[0076] The negative electrode film-forming additive can form an SEI film on the surface of the negative electrode active material by generating a film-forming reaction on the surface of the negative electrode active material. The SEI film coats the surface of the negative electrode active material in situ, thereby stabilizing the structure of the negative electrode active material, reducing the risk of persistent side reactions between the negative electrode active material and the electrolyte, and ensuring the electrochemical performance of the negative electrode active material. In addition, the negative electrode film-forming additive may include a lithium salt-based additive. The SEI film formed on the negative electrode has a small impedance, which is more favorable for the insertion and desorption of lithium ions.

[0077] The cathode film-forming additive can form a cathode solid electrolyte interphase (CEI) film on the surface of the cathode active material by generating a film-forming reaction on the surface of the cathode active material. The CEI film coats the surface of the cathode active material in situ, which not only stabilizes the structure of the cathode active material, but also reduces the risk of the electrolyte corroding the cathode active material due to the decomposition of the electrolyte and dissolving the transition metals in the cathode active material, and further protects the cathode active material and ensures the electrochemical performance of the cathode active material.

[0078] In this application, the CEI film and the SEI film are collectively referred to as interfacial films.

[0079] In the present application, when the content of the negative electrode film-forming additive and the positive electrode film-forming additive is adjusted to satisfy the above formula, the electrolyte can form an SEI film on the surface of the negative electrode active material, and a CEI film on the surface of the positive electrode active material. In addition, the interfacial impedance of the two kinds of film layers is relatively low, the kinetic activity is good, and the charge transfer impedance in the secondary battery is small, which is favorable for the rapid movement of lithium ions, and can improve the rapid charging performance of the secondary battery. Preferably, 1≦b2 / b1≦40, and for example, b2 / b1 can be 1, 2, 3, 5, 8, 10, 15, 20, 22, 25, 28, 30, 32, 35, 40, 42, 45, 48, 50, 52, 55, 58 or 60, or can be within a range consisting of any two of the above values.

[0080] In some embodiments, 0.01≦b1≦1.5.

[0081] When the negative electrode film-forming additive is in the above range, it is possible to form a dense and stable SEI film on the surface of the negative electrode active material, sufficiently protect the negative electrode active material, improve the structural stability of the negative electrode active material, and ensure the cycle stability of the secondary battery. Preferably, 0.1≦b1≦1.2. Exemplarily, the mass percentage content b1% of the negative electrode film-forming additive may be 0.01%, 0.05%, 0.1%, 0.5%, 0.8%, 1%, 1.2%, 1.3% or 1.5%, or may be within a range consisting of any two of the above values.

[0082] In some embodiments, 0.1≦b2≦7.

[0083] When the positive electrode film-forming additive is in the above range, it is possible to form a dense and stable CEI film on the surface of the positive electrode active material, which can fully protect the positive electrode active material, improve the structural stability of the positive electrode active material, and ensure the cycle stability of the secondary battery. Preferably, 0.5≦b2≦5. Exemplarily, the mass percentage content b2% of the positive electrode film-forming additive may be 0.1%, 0.5%, 0.8%, 1%, 1.2%, 1.3%, 1.5%, 2%, 2.5%, 3%, 3.5%, 4%, 4.5%, 5%, 5.5%, 6%, 6.5% or 7%, or may be within a range consisting of any two of the above values.

[0084] Examples of the negative electrode film-forming additive include one or more of a boron-containing lithium salt, a phosphorus-containing lithium salt, and a sulfur-containing lithium salt.

[0085] The boron-containing lithium salt is a lithium salt with a B atom as the central atom, and can be coordinated with an alkoxy group, o-diphenol, o-hydroxy group, carboxylic acid, etc. to form an anion complex. The anion complex is mainly a large π-conjugated structure, and the negative charge distribution of the central ion is relatively dispersed, the charge is delocalized, and the anion radius is large, so that the anion is less likely to form a strong ion pair with the lithium ion in an organic solvent, and its solubility is relatively good. The more electron-withdrawing groups there are in the anion complex, the more stable the anion structure is, and the higher the solubility of the lithium ion in the electrolyte, which is favorable for improving the conductivity of the electrolyte. In addition, the boron-containing lithium salt can form a high-performance SEI film on the surface of the negative electrode active material. The SEI film is insoluble in organic solvents and can exist stably in the organic electrolyte, so it can effectively reduce the insertion of solvent molecules in the electrolyte into the negative electrode active material, ensure the structural stability of the negative electrode active material, and further improve the cycle performance of the secondary battery.

[0086] The phosphorus-containing lithium salt additive has a relatively large anion group and high ionic conductivity, which is advantageous for further improving the dynamic performance of the electrolyte, and the phosphorus-containing lithium salt additive can form a CEI film on the surface of the positive electrode active material, and the formed CEI film has high lithium ion conductivity, which can significantly inhibit the continuous decomposition of the electrolyte, reduce the elution of transition metal ions in the positive electrode active material, and improve the cycle performance of the secondary battery.In addition, the phosphorus-containing lithium salt additive can also form an SEI film on the surface of the negative electrode active material, which has low interface impedance, and can significantly improve the cycle performance of the battery.

[0087] The sulfur-containing lithium salt additive has excellent oxidation resistance, high thermal stability, and is not sensitive to water in the electrolyte, so it is unlikely to cause side reactions.In addition, the sulfur-containing lithium salt additive has a relatively high electrical conductivity, which is favorable for improving the migration speed of lithium ions and can improve the dynamic performance of the electrolyte.

[0088] Examples of boron-containing lithium salts include lithium tetrafluoroborate (LiBF4), lithium disoxalate borate (LiB(C2O4)2, abbreviated as LiBOB), and lithium difluorooxalate borate (LiC2O4F2, abbreviated as LiDFOB). Further, the boron-containing lithium salts include compositions of lithium tetrafluoroborate LiBF4, lithium disoxalate borate (LiB(C2O4)2, abbreviated as LiBOB), and lithium difluorooxalate borate (LiC2O4F2, abbreviated as LiDFOB).

[0089] When lithium tetrafluoroborate LiBF4 is used in combination with an organic solvent in the electrolyte, such as a carbonate-based solvent or additive, the viscosity of the system made of lithium tetrafluoroborate is relatively low, which is favorable for the release of lithium ions and improves the electrical conductivity in the electrolyte. The SEI film formed by lithium tetrafluoroborate has a relatively uniform thickness, relatively good kinetic activity, and relatively small charge transfer impedance in the secondary battery, which can significantly improve the low-temperature performance of the secondary battery. The SEI film is not easily thermally decomposed and has relatively stable performance at high temperatures, which can significantly improve the high-temperature performance of the secondary battery.

[0090] Either one of lithium disoxalate borate LiBOB and lithium difluorooxalate borate LiDFOB has a passivation effect on the positive electrode current collector in the positive electrode sheet, so that the risk of corrosion of the positive electrode current collector due to a side reaction with the positive electrode current collector can be reduced and the structural stability of the positive electrode sheet can be improved. In addition, an electrolyte containing either one of lithium disoxalate borate LiBOB and lithium difluorooxalate borate LiDFOB is less likely to generate acidic substances and can further reduce the risk of corrosion of the positive electrode current collector. Lithium disoxalate borate LiBOB and lithium difluorooxalate LiDFOB have good compatibility with the positive electrode active material, are favorable for the movement of lithium ions, and can form an effective SEI film on the surface of the negative electrode active material, thereby improving the protective performance for the negative electrode active material.

[0091] When lithium tetrafluoroborate (LiBF4), lithium disoxalate borate (LiBOB) and lithium difluorooxalate borate (LiDFOB) are used in combination, the SEI film formed by the three contains many components, making the structure of the SEI film more stable. In addition to ensuring the stability of the structure, the impedance value of the SEI film is relatively small, and the low-temperature performance of the secondary battery can be ensured.

[0092] When the secondary battery of the present application contains the above boron-containing lithium salt, an SEI film having a stable structure and a relatively small impedance value is formed on the surface of the negative electrode active material, thereby improving the high and low temperature performance of the secondary battery.

[0093] As examples of phosphorus-containing lithium salts, the phosphorus-containing lithium salts may include one or more of lithium difluorophosphate LiPO2F2, lithium fluorophosphate Li2PO3F, and lithium phosphate Li3PO4.

[0094] The phosphorus-containing lithium salt is an inorganic lithium phosphate salt, and Li x PO y F z The SEI film can form an SEI film rich in LiF components with LiF, and the SEI film has a low interface impedance, which can significantly improve the cycle performance of the secondary battery. In addition, during the initial charging process of the secondary battery, the CEI film can be involved in the film formation of the positive electrode and form a stable and low impedance CEI film, which can effectively reduce the oxidative decomposition of the electrolyte, for example, the side reaction between the carbonate ester solvent in the electrolyte and the surface of the positive electrode active material, thereby ensuring the structural stability of the electrolyte, mitigating the destruction of the positive electrode active material, and improving the cycle performance of the secondary battery.

[0095] As examples of sulfur-containing lithium salts, the sulfur-containing lithium salts may include one or more of lithium fluorosulfonate LiFSO3, lithium sulfate Li2SO4, and lithium sulfamate LiSO3NH2.

[0096] The sulfur-containing lithium salt can form a dense and stable SEI film on the surface of the negative electrode active material, and can further improve the protective performance for the negative electrode active material.

[0097] In some embodiments, the positive electrode film-forming additive includes a carbonate-based additive and / or a sulfate-based additive.

[0098] The carbonate-based additive includes one or more of vinylene carbonate VC, fluoroethylene carbonate FEC, difluoroethylene carbonate DFEC, vinylethylene carbonate VEC and dioctyl carbonate CC. The carbonate-based additive can form a dense and stable film layer and can provide good protection for active materials. In addition, the carbonate-based additive has a strong dielectric constant and dissolves lithium salt to a greater extent, so that the lithium salt can dissociate lithium ions more easily, improving the conductivity of the electrolyte, and can be mixed with the first organic solvent to better adjust the dielectric constant and viscosity of the electrolyte, improving the ionic conductivity of the secondary battery, and further improving the electrochemical window of the secondary battery.

[0099] The sulfate additive comprises a cyclic sulfonate additive and / or a hydrocarbon sulfate additive, the cyclic sulfonate additive comprises one or more of 1,3-propane sultone PS, propylene sultone PES, and 3-fluoro-1,3-propane sultone FPS, and the hydrocarbon sulfate additive comprises one or more of vinyl sulfate DTD, diethyl sulfate DES, and dimethyl sulfate DMS. The sulfate additive can form a dense and stable membrane layer and can provide good protection for active materials.

[0100] In some embodiments, the electrolyte may further include a lithium salt, the lithium salt including at least one of lithium hexafluorophosphate (LiPF6), lithium bisfluorosulfonylimide (LiFSI), and lithium bistrifluoromethylsulfonylimide (LiTFSI).

[0101] Lithium salts are considered to be a combination of lithium ions and anionic groups, and have an important effect on the electrolyte. The lithium salts have thermal stability and high electrical conductivity.

[0102] In some embodiments, the mass percentage content of the lithium salt relative to the total mass of the electrolyte is represented by d%, and is 5%≦d≦25%, and more preferably 10%≦d≦20%.

[0103] When the mass percentage content of the lithium salt is in the above range, it is favorable for the rapid movement of lithium ions, while the lithium salt can form an interfacial film on the surface of the active material together with other substances to stabilize the active material.Preferably, 10%≦d≦20%, and illustratively, the mass percentage content d% of the lithium salt can be 5%, 6%, 7%, 8%, 9%, 10%, 12%, 13%, 15%, 16%, 18%, 20%, 21%, 22%, 24% or 25%, or can be within any two of the above numerical ranges.

[0104] The electrolyte of the present application can be prepared according to a conventional method in this field. For example, the additive, the solvent, the electrolyte salt, etc. can be mixed uniformly to obtain the electrolyte. The order of addition of each substance is not particularly limited, and for example, the additive, the electrolyte salt, etc. can be added to the non-aqueous solvent and mixed uniformly to obtain the non-aqueous electrolyte.

[0105] In the present application, each component and its content in the electrolyte solution can be measured according to a method known in the art, for example, gas chromatography-mass spectrometry (GC-MS), ion chromatography (IC), liquid chromatography (LC), nuclear magnetic resonance spectroscopy (NMR), etc.

[0106] In addition, when testing the electrolyte of the present application, a freshly prepared electrolyte may be directly obtained, or the electrolyte may be obtained from a secondary battery. One exemplary method for obtaining the electrolyte from a secondary battery includes a step of discharging the secondary battery to a discharge cut-off voltage (for safety reasons, the battery is generally placed in a fully discharged state), centrifuging the battery, and then extracting an appropriate amount of the liquid obtained by the centrifugation as the nonaqueous electrolyte. The nonaqueous electrolyte may be directly obtained from the electrolyte inlet of the secondary battery.

[0107] [Positive electrode sheet]

[0108] In some embodiments, the positive electrode sheet includes a positive electrode current collector and a positive electrode film layer provided on at least one surface of the positive electrode current collector. For example, the positive electrode current collector has two surfaces facing each other in the thickness direction, and the positive electrode film layer is provided on either one or both of the two facing surfaces of the positive electrode current collector.

[0109] The positive electrode film layer includes a positive electrode active material, and the positive electrode active material can be a positive electrode active material for secondary batteries known in the art. For example, the positive electrode active material may include at least one of lithium transition metal oxide, lithium-containing phosphate with an olivine structure, and modified compounds thereof. The lithium transition metal oxide is, for example, at least one of lithium cobalt oxide, lithium nickel oxide, lithium manganese oxide, lithium nickel cobalt oxide, lithium manganese cobalt oxide, lithium nickel manganese oxide, lithium nickel cobalt manganese oxide, lithium nickel cobalt aluminum oxide, and modified compounds thereof. Examples of lithium-containing phosphate with an olivine structure include lithium iron phosphate, a composite material of lithium iron phosphate and carbon, lithium manganese phosphate, a composite material of lithium manganese phosphate and carbon, lithium manganese iron phosphate, a composite material of lithium manganese iron phosphate and carbon, and at least one of modified compounds thereof. The present application is not limited to these materials, and conventionally known materials used as positive electrode active materials for other secondary batteries can be used. These positive electrode active materials may be used alone or in combination of two or more.

[0110] In some embodiments, the positive electrode active material is LiNi x Co y Mn z M 1-x-y-z O2 or LiNi a Co b Al c N 1-a-b-cO2, where M and N are each independently any one selected from Co, Ni, Mn, Mg, Cu, Zn, Al, Sn, B, Ga, Cr, Sr, V, and Ti, and 0≦y≦1, 0≦x<1, 0≦z≦1, x+y+z≦1, 0≦a≦1, 0≦b≦1, 0≦c≦1, a+b+c≦1. When a boron-containing lithium salt is blended into the positive electrode active material, the B atom in the boron-containing lithium salt is easily bonded to the O atom in the positive electrode active material, thereby reducing the charge transfer resistance of the positive electrode active material and reducing the diffusion resistance of lithium ions in the positive electrode active material phase. Therefore, when the non-aqueous electrolyte contains an appropriate content of lithium tetrafluoroborate and lithium difluorooxalate borate, the low cobalt or cobalt-free positive electrode active material has a significantly improved lithium ion diffusion rate, so that the lithium ions in the phase of the low cobalt or cobalt-free positive electrode active material are timely replenished to the surface, and the crystal structure of the low cobalt or cobalt-free positive electrode active material can be stabilized by avoiding the over-lithiation on the surface of the low cobalt or cobalt-free positive electrode active material. Since the crystal structure of the low cobalt or cobalt-free positive electrode active material is more stable, the occurrence of over-lithiation on the surface of the low cobalt or cobalt-free positive electrode active material can be greatly reduced, which can greatly reduce the occurrence probability of problems such as the occurrence of irreversible distortion of the positive electrode active material and the increase in lattice defects.

[0111] LiNi x Co y Mn z M 1-x-y-z O2 or LiNi a Co b Al c N 1-a-b-c O2 can be prepared according to conventional methods in the field. An exemplary preparation method includes mixing a lithium source, a nickel source, a cobalt source, a manganese source, an aluminum source, an M element precursor, and an N element precursor, followed by sintering. The sintering atmosphere may be an oxygen-containing atmosphere, for example, an air atmosphere or an oxygen atmosphere. The O2 concentration of the sintering atmosphere is, for example, 70% to 100%. The sintering temperature and sintering time can be adjusted according to the actual situation.

[0112] By way of example, the lithium source includes at least one of lithium oxide (Li2O), lithium phosphate (Li3PO4), lithium dihydrogen phosphate (LiH2PO4), lithium acetate (CH3COOLi), lithium hydroxide (LiOH), lithium carbonate (Li2CO3), and lithium nitrate (LiNO3). By way of example, the nickel source includes at least one of nickel sulfate, nickel nitrate, nickel chloride, nickel oxalate, and nickel acetate, but is not limited thereto. By way of example, the cobalt source includes at least one of cobalt sulfate, cobalt nitrate, cobalt chloride, cobalt oxalate, and cobalt acetate, but is not limited thereto. By way of example, the manganese source includes at least one of manganese sulfate, manganese nitrate, manganese chloride, manganese oxalate, and manganese acetate, but is not limited thereto. By way of example, the aluminum source includes at least one of aluminum sulfate, aluminum nitrate, aluminum chloride, aluminum oxalate, and aluminum acetate, but is not limited thereto. By way of example, the precursor of the M element includes, but is not limited to, at least one of an oxide, a nitrate compound, a carbonate compound, a hydroxide, and an acetate compound of the M element. By way of example, the precursor of the N element includes, but is not limited to, at least one of ammonium fluoride, lithium fluoride, hydrogen fluoride, ammonium chloride, lithium chloride, hydrogen chloride, ammonium nitrate, ammonium nitrite, ammonium carbonate, ammonium hydrogen carbonate, ammonium phosphate, phosphoric acid, ammonium sulfate, ammonium hydrogen sulfate, ammonium hydrogen sulfite, ammonium sulfite, ammonium hydrogen sulfide, hydrogen sulfide, lithium sulfide, ammonium sulfide, and elemental sulfur.

[0113] In some embodiments, the positive electrode layer has the molecular formula LiNi x Co y Mn z M 1-x-y-z O2 or LiNi a Co b Al c N 1-a-b-cThe mass percentage content of O2 in layered materials is 80% to 99%. For example, the molecular formula is LiNi x Co y Mn z M 1-x-y-z O2 or LiNi a Co b Al c N 1-a-b-c The mass percentage content of the layered material that is O2 may be 80%, 81%, 82%, 83%, 84%, 85%, 86%, 87%, 88%, 89%, 90%, 91%, 92%, 93%, 94%, 95%, 96%, 97%, 98%, 99% or any range of values ​​greater than or equal to ... x Co y Mn z M 1-x-y-z O2 or LiNi a Co b Al c N 1-a-b-c The mass percentage content of the layered material which is O2 is 85%-99%, 90%-99%, 95%-99%, 80%-98%, 85%-98%, 90%-98%, 95%-98%, 80%-97%, 85%-97%, 90%-97% or 95%-97%.

[0114] In some embodiments, the positive electrode film layer may include a positive electrode conductive agent if necessary. In the present application, the type of the positive electrode conductive agent is not particularly limited, and as an example, the positive electrode conductive agent includes one or a combination of a plurality of types selected from superconducting carbon, conductive graphite, acetylene black, carbon black, ketjen black, carbon dots, carbon nanotubes, graphene, and carbon nanofibers. In some embodiments, based on the total mass of the positive electrode film layer, the mass percentage content of the positive electrode conductive agent is 5% or less.

[0115] In some embodiments, the positive electrode membrane layer may include a positive electrode adhesive if necessary. In the present application, the type of the positive electrode adhesive is not particularly limited, and as an example, the positive electrode adhesive may include one or more combinations selected from polyvinylidene fluoride (PVDF), polytetrafluoroethylene (PTFE), vinylidene fluoride-tetrafluoroethylene-propylene terpolymer, vinylidene fluoride-hexafluoropropylene-tetrafluoroethylene terpolymer, tetrafluoroethylene-hexafluoropropylene copolymer, and fluorine-containing acrylate resin. In some embodiments, based on the total mass of the positive electrode membrane layer, the mass percentage content of the positive electrode adhesive is 5% or less.

[0116] In some embodiments, the positive electrode current collector may be a metal foil or a composite current collector. Examples of the metal foil include aluminum foil and aluminum alloy foil. The composite current collector may include a polymeric material base layer and a metal material layer formed on at least one surface of the polymeric material base layer. As an example, the metal material may include one or more combinations selected from aluminum, aluminum alloy, nickel, nickel alloy, titanium, titanium alloy, silver, and silver alloy. The polymeric material base layer may include one or more combinations selected from polypropylene (PP), polyethylene terephthalate (PET), polybutylene terephthalate (PBT), polystyrene (PS), and polyethylene (PE).

[0117] The positive electrode membrane layer is typically formed by applying a positive electrode slurry to a positive electrode current collector, drying, and cold pressing. The positive electrode slurry is typically formed by dispersing a positive electrode active material, an optional conductive agent, an optional adhesive, and any other components in a solvent, and stirring the mixture uniformly. The solvent may be, but is not limited to, N-methylpyrrolidone (NMP).

[0118] [Negative electrode sheet]

[0119] The negative electrode sheet includes a negative electrode current collector and a negative electrode film layer provided on at least one surface of the negative electrode current collector and including a negative electrode active material.

[0120] As an example, the negative electrode current collector has two surfaces opposing each other in the thickness direction thereof, and the negative electrode film layer is provided on either one or both of the two opposing surfaces of the negative electrode current collector.

[0121] In some embodiments, the negative electrode active material may be a battery negative electrode active material known in the art. As an example, the negative electrode active material may include at least one of artificial graphite, natural graphite, soft carbon, hard carbon, silicon-based material, tin-based material, lithium titanate, and lithium aluminum alloy. The silicon-based material may be at least one selected from elemental silicon, silicon oxide, silicon carbon composite, silicon nitrogen composite, and silicon alloy. The tin-based material may be at least one selected from elemental tin, tin oxide, and tin alloy. However, the present application is not limited to these materials, and other conventional materials that can be used as a negative electrode active material for a battery may be used. These negative electrode active materials may be used alone or in combination of two or more types.

[0122] In some embodiments, the negative electrode membrane layer may include a negative electrode adhesive, if necessary. In the present application, the type of the negative electrode adhesive is not particularly limited. For example, the negative electrode adhesive may include one or more combinations selected from styrene butadiene rubber (SBR), water-soluble unsaturated resin SR-1B, water-soluble acrylic resin (e.g., polyacrylic acid PAA, polymethacrylic acid PMAA, sodium polyacrylate PAAS), polyacrylamide (PAM), polyvinyl alcohol (PVA), sodium alginate (SA), and carboxymethyl chitosan (CMCS). In some embodiments, based on the total mass of the negative electrode membrane layer, the mass percentage content of the negative electrode adhesive is 5% or less.

[0123] In some embodiments, the negative electrode film layer may include a negative electrode conductive agent if necessary. In the present application, the type of the negative electrode conductive agent is not particularly limited, and as an example, the negative electrode conductive agent may include one or a combination of a plurality of types selected from superconducting carbon, conductive graphite, acetylene black, carbon black, ketjen black, carbon dots, carbon nanotubes, graphene, and carbon nanofibers. In some embodiments, based on the total mass of the negative electrode film layer, the mass percentage content of the negative electrode conductive agent is 5% or less.

[0124] In some embodiments, the negative electrode membrane layer may include other auxiliary agents as necessary. For example, the other auxiliary agents may include a thickener, such as sodium carboxymethylcellulose (CMC-Na), a PTC thermistor material, etc. In some embodiments, based on the total mass of the negative electrode membrane layer, the mass percentage content of the other auxiliary agents is 2% or less.

[0125] In some embodiments, the negative electrode current collector may be a metal foil or a composite current collector. Examples of the metal foil include copper foil and copper alloy foil. The composite current collector may include a polymeric material base layer and a metal material layer formed on at least one surface of the polymeric material base layer. As an example, the metal material may include one or more combinations selected from copper, copper alloy, nickel, nickel alloy, titanium, titanium alloy, silver, and silver alloy. The polymeric material base layer may include one or more combinations selected from polypropylene (PP), polyethylene terephthalate (PET), polybutylene terephthalate (PBT), polystyrene (PS), and polyethylene (PE).

[0126] The negative electrode membrane layer is typically formed by applying a negative electrode slurry to a negative electrode current collector, drying, and cold pressing. The negative electrode slurry is typically formed by dispersing the negative electrode active material, optional conductive agent, optional adhesive, and other optional auxiliary agents in a solvent and stirring uniformly. The solvent may be, but is not limited to, N-methylpyrrolidone (NMP) or deionized water.

[0127] The negative electrode sheet does not exclude additional functional layers other than the negative electrode film layer. For example, in some embodiments, the negative electrode sheet further includes a protective layer covering the surface of the negative electrode film layer.

[0128] [Separator]

[0129] In some embodiments, the secondary battery further includes a separator. In the present application, the type of the separator is not particularly limited, and any known porous structure separator having good chemical stability and mechanical stability can be selected.

[0130] In some embodiments, the separator includes a substrate layer and a coating layer provided on a surface of the substrate layer, the substrate of the substrate layer includes one or more of polyethylene, polypropylene, polyparaphenylene terephthalamide, polyethylene terephthalate, polytetrafluoroethylene, polyacrylonitrile, polyimide, and polyamide, and the coating layer includes a ceramic coating layer and / or a polymer coating layer.

[0131] The substrate layer has good permeability to lithium ions, which is favorable for the movement of lithium ions, and a coating layer is provided on the surface of the substrate layer, which can further improve the mechanical properties of the separator.

[0132] Preferably, the ceramic particles in the ceramic coating layer comprise one or more of SiO2, Al2O3, AlOOH, CaO, TiO2, MgO, ZnO, ZrO2, Mg(OH)2, and BaSO4.

[0133] Preferably, the polymer material of the polymer coating layer includes one or more of polyethylene PE, polypropylene PP, polyparaphenylene terephthalamide PPTA, polyethylene terephthalate PET, polytetrafluoroethylene PTFE, polyacrylonitrile PAN, polyimide PI and polyamide PA. The polymer coating layer can be selected from the same or different materials as the substrate layer. The thicknesses of the polymer coating layer and the substrate layer can be different, and preferably, the thickness of the polymer coating layer is smaller than the thickness of the substrate layer.

[0134] In another embodiment, the material of the separator may be at least one selected from glass fiber, nonwoven fabric, polyethylene, polypropylene, and polyvinylidene fluoride. The separator may be a single-layer film or a multi-layer composite film, but is not particularly limited. When the separator is a multi-layer composite film, the materials of each layer may be the same or different, but is not particularly limited.

[0135] In some embodiments, the positive electrode sheet, the negative electrode sheet, and the separator can be produced into an electrode assembly by a winding process or a lamination process.

[0136] In some embodiments, the secondary battery may have an exterior packaging, which is used to seal the electrode assembly and electrolyte.

[0137] In some embodiments, the exterior of the secondary battery may be a hard case, such as a hard plastic case, an aluminum case, a steel case, etc. The exterior of the secondary battery may be a soft pack, such as a bag-type soft pack. The material of the soft pack may be plastic, such as polypropylene, polybutylene terephthalate, and polybutylene succinate.

[0138] In the present application, the shape of the secondary battery is not particularly limited, and may be cylindrical, rectangular, or any other shape. Fig. 1 shows a secondary battery 5 having a rectangular structure as an example.

[0139] In some embodiments, as shown in FIG. 1 and FIG. 2, the exterior may include a housing 51 and a cover plate 53. The housing 51 may include a bottom plate and a side plate connected to the bottom plate, and the bottom plate and the side plate surround and form a receiving cavity. The housing 51 has an opening communicating with the receiving cavity, and the cover plate 53 covers the opening to close the receiving cavity. The positive electrode sheet, the negative electrode sheet, and the separator can form an electrode assembly 52 by a winding process or a stacking process. The electrode assembly 52 is packaged in the receiving cavity. The electrolyte is impregnated in the electrode assembly 52. ​​The number of electrode assemblies 52 included in the secondary battery 5 may be one or more, and can be adjusted as needed.

[0140] The method of manufacturing the secondary battery of the present application is known. In some embodiments, a secondary battery can be formed by assembling a positive electrode sheet, a separator, a negative electrode sheet, and an electrolyte. As an example, a positive electrode sheet, a separator, and a negative electrode sheet are wound or laminated to form an electrode assembly, the electrode assembly is placed in an outer casing, dried, and then an electrolyte is injected, followed by vacuum sealing, standing, chemical formation, shaping, and other processes to obtain a secondary battery.

[0141] In some embodiments of the present application, the secondary battery of the present application may be assembled into a battery module, and the number of secondary batteries included in the battery module may be multiple, and the specific number may be adjusted according to the application and capacity of the battery module.

[0142] Fig. 3 is a schematic diagram of an example battery module 4. As shown in Fig. 3, in the battery module 4, the multiple secondary batteries 5 may be arranged in sequence along the longitudinal direction of the battery module 4. Of course, they may be arranged in any other manner. Furthermore, the multiple secondary batteries 5 may be fixed by fasteners.

[0143] Optionally, the battery module 4 may further include a case having an accommodation space for accommodating a plurality of secondary batteries 5.

[0144] In some embodiments, the battery modules may be assembled into a battery pack, and the number of battery modules included in the battery pack can be adjusted according to the application and capacity of the battery pack.

[0145] 4 and 5 are schematic diagrams of an example battery pack 1. As shown in Fig. 4 and 5, the battery pack 1 may include a battery box and a plurality of battery modules 4 provided in the battery box. The battery box includes an upper housing 2 and a lower housing 3, and the upper housing 2 covers the lower housing 3 to form an enclosed space for accommodating the battery modules 4. The plurality of battery modules 4 may be arranged in the battery box in any manner.

[0146] power consumption equipment

[0147] In a second aspect, the present application provides a power consumption device including at least one of the secondary battery, battery module, and battery pack of the present application. The secondary battery, battery module, and battery pack may be used as a power source for the power consumption device, or may be used as an energy storage means for the power consumption device. The power consumption device may be, but is not limited to, a mobile device (e.g., a mobile phone, a laptop, etc.), an electric vehicle (e.g., a pure electric vehicle, a hybrid electric vehicle, a plug-in hybrid electric vehicle, an electric bicycle, an electric scooter, an electric golf cart, an electric truck, etc.), a train, a ship, a satellite, an energy storage system, etc.

[0148] A power consuming device can select a secondary battery, a battery module or a battery pack according to its usage needs.

[0149] 6 is a schematic diagram of an example power consumption device 6, such as a pure electric vehicle, a hybrid electric vehicle, or a plug-in hybrid electric vehicle, etc. A battery pack 1 or a battery module can be employed to meet the high power and high energy density requirements of the power consumption device.

[0150] Other examples of power consuming devices may be mobile phones, tablet computers, notebook computers, etc. These power consuming devices are generally required to be thin and can use secondary batteries as their power source.

[0151] Working Example

[0152] The following examples are provided to more specifically describe the contents of the present application, and these examples are merely used for explanatory purposes, and it is obvious to those skilled in the art that various modifications and changes can be made within the scope of the contents of the present application.Unless otherwise specified, all parts, percentages, and ratios described in the following examples are calculated based on mass, and all reagents used in the examples can be purchased or synthesized according to conventional methods and can be used directly without further processing, and all devices used in the examples can be purchased.

[0153] Example 1

[0154] 1. Preparation of Positive Electrode Sheet

[0155] As the positive electrode current collector, an aluminum foil having a thickness of 12 μm was used.

[0156] Positive electrode active material LiNi 0.65 Co 0.07 Mn 0.28The conductive agent, carbon black, and adhesive, polyvinylidene fluoride (PVDF), were mixed in a weight ratio of 97.5:1.4:1.1 in an appropriate amount of NMP as a solvent by thorough stirring to form a uniform positive electrode slurry. The positive electrode slurry was then uniformly applied to the surface of an aluminum foil as a positive electrode current collector, and after drying and cold pressing, a positive electrode sheet was obtained.

[0157] 2. Preparation of negative electrode sheet

[0158] A copper foil with a thickness of 8 μm was used as the negative electrode current collector.

[0159] The negative electrode active material graphite, the adhesive styrene butadiene rubber (SBR), the thickener sodium carboxymethylcellulose (CMC-Na), and the conductive agent carbon black (SuperP) were mixed in a weight ratio of 96.2:1.8:1.2:0.8 with an appropriate amount of solvent and deionized water and stirred thoroughly to form a uniform negative electrode slurry. The negative electrode slurry was then uniformly applied to the surface of the copper foil, which was the negative electrode current collector, and dried and cold pressed to obtain a negative electrode sheet.

[0160] 3. Separator

[0161] A porous polyethylene (PE) film was used as the separator.

[0162] 4. Preparation of electrolyte

[0163] In an environment with a water content of less than 10 ppm, non-aqueous organic solvents ethylene carbonate, ethyl methyl carbonate, and diethyl carbonate were mixed in a volume ratio of 1:1:1 to obtain an electrolyte solvent, and additives were dissolved in the mixed solvent to prepare an electrolyte with a lithium salt concentration of 1 mol / L. For specific substances contained in the electrolyte, see the table below.

[0164] 5. Preparation of secondary batteries

[0165] The positive electrode sheet, separator, and negative electrode sheet are stacked in this order, with the separator positioned between the positive electrode sheet and the negative electrode sheet to perform isolation, and then wound to obtain an electrode assembly. The electrode assembly is placed in an exterior case, dried, and then an electrolyte is injected. The lithium-ion battery is obtained through processes such as vacuum sealing, standing, chemical formation, and shaping.

[0166]

[0167] Example 2

[0168] Examples 2-1 to 2-8

[0169] The secondary battery was prepared in a similar manner to that of Example 1, except that the porosity ε% of the "separator" was adjusted and 4≦(b*ε) / c≦240. See Tables 1 to 3 for specific parameters.

[0170] Comparative Example

[0171] Comparative Example 1 and Comparative Example 2

[0172] The secondary battery was prepared in a similar manner to Example 1, except that the porosity ε% of the “separator” was adjusted. See Tables 1 to 3 for specific parameters.

[0173] Example 3

[0174] Examples 3-1 to 3-7

[0175] The secondary battery was prepared in a similar manner to Example 1, except that the mass percentage content b1% of the "negative electrode film-forming additive" was adjusted. Specific parameters are shown in Tables 1 to 3.

[0176] Example 4

[0177] Examples 4-1 to 4-7

[0178] The secondary battery was prepared in a similar manner to Example 1, except that the mass percentage content b2% of the “positive electrode film-forming additive” was adjusted. See Tables 1 to 3 for specific parameters.

[0179] Example 5

[0180] Examples 5-1 to 5-3

[0181] The secondary battery was prepared in a similar manner to Example 1, except that the mass percentage content a % of the "first organic solvent" was adjusted. See Tables 1 to 3 for specific parameters.

[0182] [Table 1]

[0183] In Table 1, b1=b11+b12+b13.

[0184] [Table 2]

[0185] In Table 2, b2 = b21 + b22.

[0186] [Table 3]

[0187] In Table 3, b = b1 + b2.

[0188] Testing Department

[0189] 1.Method of measuring separator porosity ε%

[0190] It was measured using the gas displacement method according to GB / T24586. The porosity ε=(V1-V2) / V1*100%, where V1 is the apparent volume of the sample and V2 is the true volume of the sample.

[0191] 2.Method of measuring the content of each component in the electrolyte

[0192] After taking the freshly prepared electrolyte solution and obtaining the electrolyte solution from the secondary battery, the components of the electrolyte solution may be measured by one or more methods such as gas chromatography mass spectrometry (GC-MS), ion chromatography (IC), liquid chromatography (LC), nuclear magnetic resonance spectroscopy (NMR), etc.

[0193] Gas chromatography-mass spectrometry (GC-MS): According to GB / T-9722-2006 / GB / T6041-2002, gas chromatography and mass spectrometry are combined to separate each component in the sample by gas chromatography, and then each component is divided into fragment ions in mass spectrometry, and separated by mass-to-charge ratio (m / z) to form a specific mass spectrum diagram to obtain the qualitative analysis of each organic component in the electrolyte; then, each organic component in the electrolyte is separated in a chromatography column to generate a detection signal spectrum of each component, and the component is qualified according to retention time, and the standard is matched and the peak area is calibrated to achieve quantification, to obtain the quantitative test analysis of the organic components in the electrolyte.

[0194] Ion chromatography (IC): According to JY / T-020, detect and quantify the anions of lithium salt and lithium salt additive in the electrolyte by ion chromatography.

[0195] Nuclear magnetic resonance spectroscopy (NMR): According to JY / T0578-2020, qualitative and quantitative analysis of the components in the electrolyte is obtained.

[0196] 3. Test method for viscosity c (mPa s) of electrolyte at 25°C

[0197] At a constant temperature, the shear force generated by the spring when the rotor continues to rotate at a constant speed in the sample generates a torque, and the torque is proportional to the viscosity, which gives the viscosity value. Specifically, a Brookfield (DV-2TLV) viscometer is used to test the viscosity of the finished electrolyte. The environmental temperature is set to 25°C, and the environmental humidity is controlled to be less than 80%, 30mL of electrolyte is taken and its temperature is kept constant in a water bath pot at 25°C for at least 30min, the rotor is placed in a sample cup, the sample is placed about 0.3cm from the cup mouth, the connected viscometer is started, and a rotation speed of 70RPM is selected for testing, 10 data points are collected, and the average value of multiple points is calculated.

[0198] 4. Secondary battery cycle performance test

[0199] The secondary battery was charged at a constant current of 1C to 4.3V at 45°C, and the constant voltage charging was continued until the current became 0.05C. At this time, the secondary battery was in a fully charged state, and the charge capacity at this time was recorded and used as the first charge capacity. After leaving the secondary battery to stand for 5 minutes, it was discharged at a constant current of 1C to 2.8V, which is one cycle of charge and discharge process, and the discharge capacity at this time was recorded and used as the first discharge capacity. The secondary battery was subjected to a cycle charge and discharge test according to the above method, and the discharge capacity after each cycle was recorded. Capacity retention rate (%) of the secondary battery after 600 cycles at 25°C = discharge capacity after 600 cycles / first discharge capacity × 100%.

[0200] 5. Rapid charging performance of secondary batteries

[0201] At 25°C, the secondary battery prepared above was charged at a constant current of 0.33 C up to a charge cut-off voltage of 4.4 V, then charged at a constant voltage until the current reached 0.05 C, allowed to stand for 5 min, and further discharged at a constant current of 0.33 C up to a discharge cut-off voltage of 2.8 V, and the actual capacity was recorded as C0.

[0202] After that, the secondary battery is charged in sequence at constant currents of 0.5C0, 1C0, 1.5C0, 2C0, 2.5C0, 3C0, 3.5C0, 4C0, and 4.5C0 to the full battery charge cut-off voltage of 4.4V or the negative electrode cut-off potential of 0V (based on whichever is reached first), and after each charge is completed, it is necessary to discharge it at 1C0 to the full battery discharge cut-off voltage of 2.8V, and the SOC (State of Charge) is measured at different charge rates of 10%, 20%, 30%...80%. The negative electrode potential corresponding to the charging up to 0 V was recorded, and the charge rate-negative electrode potential curves at different SOC states were drawn and linearly fitted to obtain the charge rates corresponding to the negative electrode potential at different SOC states when the potential was 0 V. The charge rates are the charge windows at the SOC states, which are written as C10% SOC, C20% SOC, C30% SOC, C40% SOC, C50% SOC, C60% SOC, C70% SOC, and C80% SOC, respectively. The charging time T for the secondary battery to charge from 10% SOC to 80% SOC is calculated based on the formula (60 / C20% SOC+60 / C30% SOC+60 / C40% SOC+60 / C50% SOC+60 / C60% SOC+60 / C70% SOC+60 / C80% SOC)×10%. The shorter the charge time T, the better the rapid charging performance of the secondary battery.

[0203] Test Results

[0204] The effect of the present invention in improving the cycle performance and rapid charging performance of the secondary battery is shown in Table 4.

[0205] [Table 4]

[0206] As can be seen from Table 4, if the porosity of the separator in Comparative Example 1 is too small, the lithium ion migration speed in the process of passing through the separator is small, which may cause the rapid charging ability of the secondary battery to deteriorate. The solid phase transmission speed of the lithium ion can be adjusted by synergistically adjusting the porosity of the separator of the secondary battery and the mass percentage content of the film-forming additive. The liquid phase transmission speed of the lithium ion can be adjusted by adjusting the viscosity of the electrolyte. Compared to Comparative Example 2, in Examples 1 to 2-8, the porosity of the separator, the mass percentage content of the film-forming additive, and the viscosity of the electrolyte are synergistically adjusted so that 4≦(b*ε) / c≦240, especially 4≦(b*ε) / c≦180, thereby significantly improving the overall transmission speed of the lithium ion in the solid phase and the liquid phase, and improving the rapid charging ability of the secondary battery. In addition, the additive in the electrolyte forms a film on the surface of the negative electrode active material, which improves the protection performance for the negative electrode active material and improves the cycle performance of the secondary battery.

[0207] In Examples 3-1 to 3-7, by adjusting the mass percentage content b1% of the negative electrode film-forming additive, when 1≦b2 / b1≦60, especially when 1≦b2 / b1≦40, the protective ability for the negative electrode active material can be adjusted, and the cycle performance of the secondary battery can be improved.

[0208] In Examples 4-1 to 4-7, by adjusting the mass percentage content b1% of the positive electrode film-forming additive, when 1≦b2 / b1≦60, especially when 1≦b2 / b1≦40, the protective ability for the positive electrode active material can be adjusted, and the cycle performance of the secondary battery can be improved.

[0209] In Examples 5-1 and 5-3, by adjusting the mass percentage content a% of the first organic solvent, when 2≦c+2*a%≦8, the overall migration rate of lithium ions can be adjusted to improve the dynamic performance of the secondary battery.

[0210] Although the present application has been described with reference to the preferred embodiments, various modifications may be made or the components therein may be replaced with equivalents without departing from the scope of the present application. In particular, the technical features mentioned in each embodiment may be arbitrarily combined unless there is structural contradiction. The present application is not limited to the specific embodiments disclosed above, but includes all technical solutions included in the scope of the claims.

Claims

1. a positive electrode sheet including a positive electrode active material; a negative electrode sheet including a negative electrode active material; A separator provided between the positive electrode sheet and the negative electrode sheet; an electrolyte solution comprising a first organic solvent and a film-forming additive arranged to form an interfacial film on a surface of the positive electrode active material and / or the negative electrode active material; When the porosity of the separator is ε%, the mass percentage content of the film-forming additive with respect to the total mass of the electrolyte is b%, and the viscosity value of the electrolyte at 25° C. is c (mPa s), A secondary battery that satisfies 4≦(b*ε) / c≦240 and, selectably, satisfies 4≦(b*ε) / c≦180.

2. The secondary battery according to claim 1 , further satisfying at least one of conditions (1) to (3). (1) 25≦ε≦55, and optionally, 30≦ε≦50. (2) 0.1≦b≦8, and optionally, 0.1≦b≦6. (3) 1≦c≦6, and optionally, 2≦c≦5.

3. When the mass percentage content of the first organic solvent with respect to the total mass of the electrolyte solution is a%, The secondary battery according to claim 1 or 2, further satisfying 2≦c+2*a%≦8.

4. 4. The secondary battery according to claim 1, wherein 60≦a≦90, and optionally 65≦a≦85.

5. The first organic solvent includes one or more of a linear carbonate solvent, a carboxylic acid ester solvent, and a nitrile solvent; Optionally, the linear carbonate solvent comprises one or more of ethyl methyl carbonate (EMC), diethyl carbonate (DEC), dimethyl carbonate (DMC) and methyl propyl carbonate (MPC); Optionally, the carboxylic acid ester solvent comprises one or more of ethyl acetate EA, methyl acetate MA, ethyl propionate EP, methyl formate MF, ethyl butyrate EB, butyl acetate BA, methyl propionate MP, methyl butyrate MB, propyl butyrate PB, and butyl butyrate BB; Optionally, the nitrile-based solvent includes one or more of acetonitrile (AN), glutaronitrile (GLN), and adiponitrile (ADN).

6. The film-forming additive is a negative electrode film-forming additive disposed on a surface of the negative electrode active material to form an interfacial film, the negative electrode film-forming additive having a mass percentage content of b1% relative to the total mass of the electrolyte; a positive electrode film-forming additive disposed on a surface of the positive electrode active material to form an interfacial film, the positive electrode film-forming additive having a mass percentage content of b2% relative to the total mass of the electrolyte; The secondary battery according to any one of claims 1 to 5, wherein the secondary battery satisfies 1≦b2 / b1≦60, and optionally satisfies 1≦b2 / b1≦40.

7. The secondary battery according to claim 6 , wherein 0.01≦b1≦1.5 and / or 0.1≦b2≦7.

8. The negative electrode film-forming additive includes one or more of a boron-containing lithium salt, a phosphorus-containing lithium salt, and a sulfur-containing lithium salt; Optionally, the boron-containing lithium salt is lithium tetrafluoroborate, LiBF 4 , LiBOB, and LiDFOB, Optionally, the phosphorus-containing lithium salt is lithium difluorophosphate, LiPO 2 F 2 , Lithium fluorophosphate Li 2 P.O. 3 F and lithium phosphate Li 3 P.O. 4 One or more of the following: Optionally, the sulfur-containing lithium salt is lithium fluorosulfonate, LiFSO 3 , Lithium sulfate Li 2 SO 4 , lithium sulfamate LiSO 3 N.H. 2 The secondary battery according to claim 6 or 7, comprising one or more of the following:

9. The positive electrode film-forming additive includes a carbonate-based additive and / or a sulfate-based additive, Optionally, the carbonate additive comprises one or more of vinylene carbonate VC, fluoroethylene carbonate FEC, difluoroethylene carbonate DFEC, vinyl ethylene carbonate VEC, and dioctyl carbonate CC; The secondary battery according to any one of claims 6 to 8, wherein the sulfate ester-based additive selectively includes a cyclic sulfonate ester-based additive and / or a hydrocarbon group sulfate ester-based additive, and further selectively the cyclic sulfonate ester-based additive selectively includes one or more of 1,3-propane sultone PS, propylene sultone PES, and 3-fluoro-1,3-propane sultone FPS, and the hydrocarbon group sulfate ester-based additive selectively includes one or more of vinyl sulfate DTD, diethyl sulfate DES, and dimethyl sulfate DMS.

10. The electrolyte further includes a lithium salt, and the lithium salt is lithium hexafluorophosphate LiPF 6 , lithium bisfluorosulfonylimide LiFSI, and lithium bistrifluoromethylsulfonylimide LiTFSI; Optionally, the mass percentage content of the lithium salt relative to the total mass of the electrolyte is d%, where 5%≦d≦25%, and further optionally 10%≦d≦20%. The secondary battery according to any one of claims 1 to 9.

11. The separator includes a substrate layer and a coating layer provided on a surface of the substrate layer, the substrate of the substrate layer includes one or more of polyethylene, polypropylene, polyparaphenylene terephthalamide, polyethylene terephthalate, polytetrafluoroethylene, polyacrylonitrile, polyimide, and polyamide, and / or the coating layer includes a ceramic coating layer and / or a polymer coating layer, Optionally, the ceramic particles in the ceramic coating layer are SiO 2 , Al 2 O 3 , AlOOH, CaO, TiO 2 , MgO, ZnO, ZrO 2 , Mg(OH) 2 and BaSO 4 One or more of the following: The polymer material of the polymer coating layer includes one or more of polyethylene PE, polypropylene PP, polyparaphenylene terephthalamide PPTA, polyethylene terephthalate PET, polytetrafluoroethylene PTFE, polyacrylonitrile PAN, polyimide PI and polyamide PA; The secondary battery according to any one of claims 1 to 10.

12. A battery module comprising the secondary battery according to any one of claims 1 to 11.

13. A battery pack comprising the battery module according to claim 12.

14. A power consuming device comprising the secondary battery according to any one of claims 1 to 11, the battery module according to claim 12, or the battery pack according to claim 13.

Citation Information

Patent Citations

  • Nonaqueous electrolyte secondary battery

    JP2000235868A

  • Non-aqueous electrolyte secondary battery

    JP2011113667A

  • Nonaqueous electrolyte secondary battery

    JP2019050156A

  • Nonaqueous electrolyte battery

    JP2019145347A

  • Secondary battery and device comprising the secondary battery

    WO2021127996A1